Cross-modal integration in the brain is related to phonological awareness only in typical readers, not in those with reading difficulty - Mcnorgan, Chris; Randazzo-Wagner, Melissa; Booth, James R. (Frontiers in Human Neuroscience, 2013)
Fluent reading requires successfully mapping between visual orthographic and auditory phonological representations and is thus an intrinsically cross-modal process, though reading difficulty has often been characterized as a phonological deficit. However, recent evidence suggests that orthographic information influences phonological processing in typical developing (TD) readers, but that this effect may be blunted in those with reading difficulty (RD), suggesting that the core deficit underlying reading may be a failure to integrate orthographic and phonological information. Twenty-six (13 TD and 13 RD) children between 8 and 13 years of age participated in a functional magnetic resonance imaging (fMRI) experiment designed to assess the role of phonemic awareness in cross-modal processing. Participants completed a rhyme judgment task for word pairs presented unimodally (auditory only) and cross-modally (auditory followed by visual). For typically developing children, activations in a network of regions associated with processing and integrating phonology and orthography were correlated with elision (i.e. superior temporal sulcus and fusiform gyrus), a task that is particularly sensitive to phonemic awareness, but this correlation was found only in the cross-modal task. Elision was not correlated with activation for children with reading difficulty or for either group in the unimodal task. The results suggest that elision taps both phonemic awareness and cross-modal integration in typically developing readers, and that these processes are decoupled in children with reading difficulty.